Structural, morphological, and optical characterization of indium selenide (In2Se3) obtained by mechanical alloying - Josue Fernando Teoyotl Sosa; José Álvaro David Hernández de la Luz; Osvaldo López Hernández; Gabriel Juárez Diaz; Primavera López Salazar (Materials Research Express)
The optical, electrical, and thermal properties of indium selenides are strongly influenced by their crystal structure. At room temperature (RT), the indium selenide with the stoichiometry In _2 Se _2 exhibits two coexisting crystalline phases namely α and β , both can crystallize in two different crystal structures, hexagonal (2H) and rhombohedral (3 R). In polycrystalline In _2 Se _3 powders, the presence of both phases has been observed. In this study, the rhombohedral β (3 R) phase of In _2 Se _3 was synthesized by prior mechanical pulverization of powders of selenium and beads of indium, followed by mechanical alloying, achieved after 30 h of milling, and identified by x-ray diffraction (XRD). Scanning electron microscopy (SEM) revealed a morphological evolution with a predominance of agglomerates smaller than 500 nm. Photoluminescence (PL) spectra show an emission of around 1.26 eV, lower than that reported in the literature, and the optic band gap energy E _g , determined by transmission spectra and the Tauc method, was 1.23 eV, a value not previously reported for this phase.